The Energy Output from the Kuching Barrage in East Malaysia - Samo, K. A.; Keerio, M. U.; Shaikh, S. A.; Rigit, A. R. H.; Mukwana, K. C. (Engineering, Technology & Applied Science Research, 2021)
Electricity generation from the sea has many advantages in comparison with other renewable energy resources. Power can be generated from new or existing barrages. Based on previous location research, a suitable system to produce tidal range energy from a potential site was developed in this paper. The main objective of this research is to calculate the energy output of the Kuching Barrage of Sarawak State of Malaysia. The daily flushing process of Kuching Barrage is conducted during the low tide period and therefore to put up the ebb generation process is appropriate. The calculated period of power generation is determined to about 6 hours. The annual energy output is calculated based on a theoretical method, with the average daily potential energy calculated to be 5.8MW and approximately 10.23GWh/year could be harnessed. This research can be beneficial for energy generation with the use of a double basin scheme for the construction of new barrages in East Malaysia.